PENGARUH STRES BERKENDARA TERHADAP PERILAKU AGRESIF PENGENDARA SEPEDA MOTOR DI KOTA DEPOK - Atika Rahmania El Barusi (Jurnal EMPATI, 2026)
Aggressive driving behavior is one of the contributing factors to the increasing number of traffic accidents, particularly in densely populated urban areas such as Depok City. High mobility in the city creates heavy and disorganized traffic conditions, which can trigger psychological pressure among motorcycle riders. This study aims to examine the effect of driving stress on aggressive driving behavior among motorcycle users in Depok City. A quantitative method with a cross-sectional design was employed. A total of 254 respondents aged 18–40 years were selected using purposive sampling. The instruments used were the Driving Stress Scale (DSS) and the Aggressive Driving Behavior Scale (ADBS). Data were analyzed using linear regression with the aid of SPSS 26. The results indicate that driving stress has a significant impact on aggressive driving behavior, accounting for 51.4% of the variance (R² = 0.514; p < 0.01). These findings indicate that the higher the level of driving stress experienced by riders, the greater their tendency to exhibit aggressive behavior on the road. This study emphasizes the importance of stress management efforts and road safety education in reducing the risk of aggressive driving behavior.